(untitled) (The Research of Medical Science Review, 2025)
Objective: To observe the levels of PIVKA-II and its correlation with various hepatic pathologies and defining relation between them. Study Design: A Cross sectional observational study Study Duration: 06 months Study Place: Tertiary Care Hospital, Lahore Methods: A cross-sectional observational study was conducted over six months in the Gastroenterology Department of a tertiary care hospital in Lahore. Using WHO Sample Size Calculator, a sample size of 312 patients was calculated. Data were analyzed using SPSS 25, with significance set at p<0.05. Ethical approval was obtained beforehand. Results: 312 patients were included in our study, among them 112 were males and 100 were females. Patients were divided into the 03 groups i.e. hepatocellular carcinoma, cirrhosis and chronic hepatitis. PIVKA-II levels were measured in all the groups. Patients with hepatocellular carcinoma showed a significant increase in levels of PIVKA-II as compared to other groups. PIVKA-II levels were ranging in 690±5 in hepatocellular group. Conclusion: PIVKA-II serves as a significant important marker in assessing diseases of liver esp liver carcinoma, cirrhosis and chronic hepatitis. Its elevation helps guide treatment protocols and further management.